Improved syntheses of high hole mobility phthalocyanines: A case of steric assistance in the cyclo-oligomerisation of phthalonitriles - Tate, Daniel J.; Anémian, Rémi; Bushby, Richard J.; Nanan, Suwat; Warriner, Stuart L.; Whitaker, and Benjamin J. (Beilstein Journal of Organic Chemistry, 2012)
It has been shown that the base-initiated cyclo-oligomerisation of phthalonitriles is favoured by bulky α-substituents making it possible to obtain the metal-free phthalocyanine directly and in high yield. The phthalocyanine with eight α-isoheptyl substituents gives a high time-of-flight hole mobility of 0.14 cm2·V−1·s−1 within the temperature range of the columnar hexagonal phase, that is 169–189 °C.
Keywords: high hole mobility; phthalocyanine; steric assistance; Thorpe–Ingold effect; time-of-flight